2006
DOI: 10.1103/physrevd.73.025004
|View full text |Cite
|
Sign up to set email alerts
|

Big bang nucleosynthesis constraints on universal extra dimensions and varying fundamental constants

Abstract: The successful prediction of light element abundances from Big Bang Nucleosynthesis (BBN) has been a pillar of the standard model of Cosmology. Because many of the relevant reaction rates are sensitive to the values of fundamental constants, such as the fine structure constant and the strong coupling constant, BBN is a useful tool to probe and to put constraints on possible cosmological variations of these constants, which arise naturally from many versions of extra-dimensional theories. In this paper, we stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 73 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…An analysis of most cosmological data (BBN, CMB, quasar etc..) assuming that the extra-dimension scales as R 0 (1 + ∆t −3/4 ) and R 0 [1+∆](1−cos ω(t−t 0 ) concluded that ∆ has to be smaller tha 10 −16 and 10 −8 respectively [304], while Ref. [328] assumes that gauge fields and matter fields can propagate in the bulk. Ref.…”
Section: Kaluza-kleinmentioning
confidence: 99%
“…An analysis of most cosmological data (BBN, CMB, quasar etc..) assuming that the extra-dimension scales as R 0 (1 + ∆t −3/4 ) and R 0 [1+∆](1−cos ω(t−t 0 ) concluded that ∆ has to be smaller tha 10 −16 and 10 −8 respectively [304], while Ref. [328] assumes that gauge fields and matter fields can propagate in the bulk. Ref.…”
Section: Kaluza-kleinmentioning
confidence: 99%
“…[6][7][8][9][10][11] for the case of two universal extra dimensions). This particular scenario has recently been studied in relation to collider phenomenology [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], indirect low-energy constraints [30][31][32][33][34][35][36][37][38][39][40][41][42][43], dark matter and cosmology [67][68][69][70][71][72][73]. It is therefore of great interest to have an implementation of the Minimal UED model (reviewed below in Section 2) in the most popular general purpose computer programs for collider and astroparticle phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…Of course our model does not directly apply to our 4d Universe. Strong constraints on isotropy during big bang nucleosynthesis should be taken into account [23,24]. Moreover, the dynamics would be certainly changed by the presence of matter on the brane.…”
Section: Introductionmentioning
confidence: 99%